A comparison of e-commerce business management and ordinary businesses from the aspects of strategic thinking / Mahathir Mahali and Junaidah Jamaluddin - Mahali, Mahathir; Jamaluddin, Junaidah (Universiti Teknologi MARA Cawangan Pahang, 2003)
Strategic thinking is merely thinking about strategy. The need for strategic thinking has never been greater. This means continuing improvement in strategic planning has profoundly changed the character of strategic planning so that it is now more appropriate to refer to it as strategic management or strategic thinking. This attempt to define strategic thinking as some kind of new and improved version of strategic planning leads to considerable confusion in attempting to elucidate the full implications of strategic thinking in its purest sense. Strategic thinking is not merely alternative nomenclature for everything falling under the umbrella of strategic management. It is a particular way of thinking with specific and clearly discernible characteristics. There is a lack of clear understanding of just what is meant by the term strategic thinking and this, in turn, has lead to considerable confusion in the strategic management arena. Thus there exists a clear need to precisely define strategic thinking so that this management paradigm can be objectively embraced and appropriately situated within the strategic management context.